Institutional Change and Ethics Management in the EU's College of Commissioners. (August 2014) - Cini, Michelle
Research Highlights and Abstract This article makes the following contribution: It identifies a gap in theoretical work on gradual institutional change by highlighting the importance of 'reluctant agency' that is, agents who do not oppose change outright, but are reluctant to agree to anything more than minimal reforms. It demonstrates the importance of the interplay of internal and external factors in explanations of gradual institutional change. It provides an empirical account of the evolution of the EU Commissioners' ethics regime since 1999. It identifies institutional change in the EU Commissioners' ethics regime as taking the form of a 'layering' process. It shows how institutional change in the EU Commissioners' ethics regime can be explained using a framework comprising political context, institutional characteristics and change agency (drawing on the work of Mahoney and Thelen). This article comprises a theory-informed case study of the European Commissioners' ethics regime. Conceptualising the evolution of the regime since 1999 as a process of gradual institutional change, it asks how the Commissioners' ethics regime continued to evolve incrementally after its inception, and what form that evolution took. Drawing on a recent theory of gradual institutional change (Mahoney and Thelen's), the article argues that the evolution of the Commissioners' ethics regime has involved a 'layering' process which has resulted from the Commission's changing position within the EU system (political context) and the extent of the Commission's control over the reform process (institutional characteristics). External change agents (the European Parliament and NGOs) are crucial, but so too is the Commission itself, which engages only reluctantly, in a risk-averse manner, in the on-going reform of the regime.